IMPACT OF CLINICAL PHARMACIST-LED EDUCATION ON HYPERTENSION KNOWLEDGE IN HYPERTENSIVE PATIENTS AT A TERTIARY CARE HOSPITAL, INDIA: A PROSPECTIVE OBSERVATIONAL STUDY - Deeptipriya Nekkanti; Challi Hareesh Srusti; Sonoma Maria K.B; Dhanush R; Pradeep Shankrappa Mannikatti; Dharitri G. Joshi; Badrish Pratap Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The prevalence of hypertension in India has been increasing recently. In response, the Ministry of Health and Family Welfare Government of India has issued guidelines for the prevention of hypertension and its complications. It is known that reducing blood pressure in hypertensive patients and improving their knowledge about hypertension can decrease the rate of cardiovascular disease and stroke complications. Methods: A prospective observational study was conducted over six months at a tertiary care hospital, enrolling 250 participants based on predefined selection criteria. The study aimed to determine the influence of leaflets and education provided by clinical pharmacists on hypertension knowledge. Participants’ knowledge of hypertension was assessed using the Hypertension Knowledge Level Scale (HK-LS). Categorical data were analyzed by Chi-square test, while quantitative variables were analyzed using paired t-test. Results: The study highlighted the positive impact of leaflets and educational interventions on hypertension knowledge, increasing from 25.2% to 77.2%. Participants with low knowledge decreased from 74.2% to 22.8% post-distribution of the Patient Information Leaflet (PIL), with the most significant improvement in the "complications" domain. Socio-demographic comparisons showed males had more knowledge than females, likely due to social and cultural factors such as employment status and a higher prevalence of hypertension among males. Education level was positively correlated with hypertension knowledge (P-value < 0.005). Conclusion: Our study highlights the need for educational guidance in disease management. Clinical pharmacists can improve patient knowledge and adherence through counselling and medication reviews, thereby reducing hypertension-related complications.